Exploring the factors influencing the application of telegram by Malaysian Tamil primary school teachers / Sri Raman Nair Chukumaran - Sri Raman Nair , Chukumaran (2023)
For this study, we sought: (1) to identify motivating, group-interactive, knowledge sharing, and confidence-increasing factors that influence teachers' use of Telegram in Malaysian Tamil Primary School; (2) to identify relationships between these determinants ("triggering event," exploration," integration," resolution. A total of 500 teachers from Malaysian Tamil Primary Schools (SJKT) took part in the workshop (SJKT). Surveys were used to collect the data. Data from the questionnaires were analyzed using SPSS and sophisticated PLS to examine the correlations between variables. A technique known as partial least squares structural equation modeling (PLS-SEM) was used to investigate factors that may influence teachers' future willingness to use Telegram. A correlational study found that instructors' attitudes of Telegram were linked to their intention to use it in the future, as well as their perception of behavioral control. Teachers' intentions to use Telegram in the future have a negligible negative link with social norm, according to the research. It is clear from the results of this study that using Telegram in the educational sector will be important in the future.